MULTIFUNCTIONAL ORCHARD MODEL FOR SYNERGISTIC PRODUCTION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The world's growing population requires increased crop yields for their feeding. In food consumption, fruit is relied upon as one of the sources of vitamins. This necessitates an increase in perennial fruit plantations. Another important product is the consumption of animal foods and products. On the other hand, a growing population is in dire need of electrical energy to meet its needs. This also requires an increase in the production of this type of energy. Worldwide, in order to protect the environment and reduce the consumption of raw materials, it is necessary to produce electricity from RES.This article discusses a model of complex production of plant production from an orchard, animal production and energy from a photovoltaic plant in a unit of arable area.; In practice, these are three separate productions to meet the needs of the population, which, however, have the same area and are located in the same place. Using the specifics of the individual productions, an attempt was made for the joint use of the areas, in which case it is possible to eliminate part of the various technological operations or serve as a basis for the other type of production. Such can be the irrigation of the plantation, the presence of shade from photovoltaics, fertilization of the plum plantation by the animals, fresh food for the animals, etc. The interrelations and the main points in the symbiotic production are given. The model can also be used in other types of joint "green" proceedings, after clarifying their specifics.